PHYSICAL ACTIVITY AND HEALTH PERCEPTION OF SCHOOL-AGE CHILDREN - Murgová, A. (Україна. Здоров’я нації, 2023)
Poor health can significantly affect the achievement of life goals. It is gratifying that studies on health and attitudes to health in children and young people are underway. It is also gratifying that the Slovak Republic has also participated in the international study HBSC - Health Behavior in School Aged Children, which is carried out in cooperation with the WHO in 43 countries. It aims to monitor the health and health-related behavior of schoolchildren in their social context. National Report HBSC Slovakia informs very clearly and transparently about the health and welfare of children and youth in various countries and shows the position of Slovakia among them. The findings of our study will serve to provide information on health and health-related behavior of schoolchildren in the Zemplín region in Slovakia and to develop effective health promotion programs, health education programs and monitor their effectiveness not only at regional, national but also international level.